A Critical Approach to the Demographics of Ageing: The Case of Oslo - Gustavo Sugahara (Cidades, Comunidades e Território)
Demographic analysis is on the basis of every city plan. It is often regarded as a technical and indisputable tool to inform policy making. In a strongly contested political environment, information on population is crucial to set priorities and define goals. However, the frequently misinterpretation, or overinterpretation, of demographic information, might also support inadequate public policy design. The increased interest on ageing in the urban context has already resulted in various initiatives all-over the world. The idea of an unsustainable “elderly boom” is a powerful narrative that is frequently used to argue for the need of improved policies for older persons. The article argues that city planners and urbanists inadequate use of demographic assessment of ageing might generate policies that can ultimately work against the interests of the older persons. I use the city of Oslo as an example of the varieties of approaches that can be used to assess ageing on a specific population. Contrary to the general assumption that Oslo will face an “elderly boom”, the study shows that the city’s ageing process today is less intense than the observed in the past. A particular attention is paid to the varieties of demographic trends observed within Oslo’s different scales.